2021
DOI: 10.1111/psyp.13799
|View full text |Cite
|
Sign up to set email alerts
|

Basal myokine levels are associated with quality of life and depressed mood in older adults

Abstract: In an aging society, late‐life depression has become an increasing problem. There is evidence that physical activity ameliorates depressive symptoms and increases the quality of life (QoL). However, the underlying mechanisms are still poorly understood. Myokines are molecules secreted in response to muscle contraction. Some of them can cross the blood‐brain barrier, making them promising candidates for mediating the beneficial effects of physical activity on mood. The present study aims to compare circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Plasma CTSB is upregulated by aerobic exercise training and associated with cognition in young adults ( 25 ). In the present study we show that CTSB is increased in late-middle-aged adults after 26 weeks of aerobic training, indicating that CTSB levels change after prolonged activity ( 25 , 54 , 55 ) whereas shorter term aerobic exercise protocols ( 56 , 57 ), and resistance training ( 58 , 59 ) show no change. The present findings in late-middle aged adults at risk for AD extend findings from healthy younger adults that CTSB levels were positively correlated with a hippocampus-dependent visual memory task after a four-month aerobic exercise intervention ( 25 ).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Plasma CTSB is upregulated by aerobic exercise training and associated with cognition in young adults ( 25 ). In the present study we show that CTSB is increased in late-middle-aged adults after 26 weeks of aerobic training, indicating that CTSB levels change after prolonged activity ( 25 , 54 , 55 ) whereas shorter term aerobic exercise protocols ( 56 , 57 ), and resistance training ( 58 , 59 ) show no change. The present findings in late-middle aged adults at risk for AD extend findings from healthy younger adults that CTSB levels were positively correlated with a hippocampus-dependent visual memory task after a four-month aerobic exercise intervention ( 25 ).…”
Section: Discussionmentioning
confidence: 45%
“…In addition, these subjects participated in a variety of athletic activities. Indeed, older marathon runners have been shown to harbor elevated CTSB levels ( 55 ). It is also noteworthy our study included both males and females, and that females may drive the myokine CTSB increase and correlations with cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,10,11 Released by concentric muscle contractions, 8 they mediate the health-promoting effects of exercise via, for example, activating IL-6-sensitive natural killer (NK) cells, 12 therefore contributing to the protection against diseases associated with low-grade inflammation. [13][14][15] Given these characteristics, myokines have also been described to belong to the group of exerkines, along with other signaling units that are released in response to exercise. 16,17 Myokines are not only released by muscle fibers, but also in the regenerating muscle from infiltrating neutrophils and macrophages, 18 fibro-adipogenic progenitors, 19 and satellite cells.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have examined the association between exercise and CTSB and reported mixed results. Chronic exercise studies have reported no changes in serum CTSB following a six-week high intensity interval training intervention [ 30 ], an inverse association between habitual exercise and plasma CTSB [ 31 ], higher levels of CTSB in older athletes compared to age-matched sedentary controls [ 32 ], and increased CTSB following twelve-weeks of resistance training [ 33 ] and twenty-six weeks of moderate-to-vigorous aerobic training [ 34 ]. Acute exercise studies have reported more consistent findings with one study reporting a significant, albeit small, increase in CTSB following a single bout of high-intensity interval training [ 35 ] and another reporting increased CTSB following an acute bout of exercise for fencers but not swimmer or sedentary individuals [ 36 ].…”
Section: Introductionmentioning
confidence: 99%